Beneficence as a source of competitive advantage. Issue 10 (7th October 2014) - Caldwell, Cam; Floyd, Larry; Taylor, Joseph; Woodard, Bryan
Abstract : Purpose: – The purpose of this paper is to define "beneficence" as a management concept that is the action associated with "benevolence" the intention. This paper explains how beneficence is a critical element for leaders in building trust. The authors identify how beneficence honors the ethical duties owed to followers and creates competitive advantage for organizations. Design/methodology/approach: – The approach of this paper is to present an extensive conceptual review of beneficence as it relates to leaders and managers and to suggest eight propositions identifying how beneficence can create competitive advantage. Findings: – The findings of this paper include eight propositions about beneficence as a source of competitive advantage. Practical implications: – The practical implications of this paper are for practitioners and scholars. This paper provides an opportunity for leaders to recognize the importance of translating good intentions into specific action in acting virtuously toward others. For scholars, this paper provides testable propositions for learning more about beneficence as a source of increased commitment, greater trust, and competitive advantage. Originality/value: – Although benevolence has been acknowledged to be a foundation of trustworthiness, benevolence is an attitude or intention. This paper explains the importance of beneficence as the action derived from benevolence as an attitude or intention to do that which benefits others.